Digital marketing transformation through artificial intelligence: A study of Nigerian small businesses - Okigbo , Ferdinand C; Mbamalu, Sophia; Iruogu, Kingsley (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This study examines the impact of Artificial Intelligence (AI) on Digital Marketing Transformation among Nigerian Small and Medium Enterprises (SMEs). Specifically, it evaluates how AI-driven customer relationship management (CRM) systems enhance digital marketing and investigates how AI-based decision-making relates to marketing transformation. Methods: The study employed a descriptive survey research design in Lagos State, Nigeria’s commercial and technological hub. From a population of 11,663 SMEs, a sample size of 371 was selected using the Krejcie and Morgan (1970) formula. Data were collected through structured questionnaires and analyzed using descriptive and inferential statistics, with hypotheses tested at a 5% significance level. Results: Findings show strong agreement that AI-enabled CRM tools enhance customer engagement, personalized service delivery, and competitive advantage. The study also found a statistically significant relationship between AI-based decision-making and digital marketing transformation, indicating that AI improves strategic precision, operational efficiency, and responsiveness to market conditions. Conclusion: AI technologies—especially CRM automation and data-driven decision-making—are vital enablers of digital marketing transformation. Their adoption strengthens customer interaction, supports predictive insights, and promotes sustainable marketing innovation among SMEs. Limitations: The study focused solely on SMEs in Lagos State, which may limit the generalizability of its findings across Nigeria. Contribution: This research provides timely empirical insight into how AI-driven CRM systems and AI-supported decision-making reshape digital marketing practices and customer relationship dynamics among Nigerian SMEs, offering implications for future technological adoption, managerial strategy, and policy development.